Effects of relay intercropping model and application of biological agents on the growth and yield of hot pepper - Nindy Sevirasari; Endang Sulistyaningsih; Budiastuti Kurniasih; Suryanti Suryanti; Arif Wibowo; Tri Joko (Jurnal Ilmu Pertanian, 2022)
Tiyung cultivar, the consumer preferences of hot pepper in Magelang Regency, is still low in productivity (7 ton.ha-1). This research aimed to determine the growth and yield of hot pepper planted in relay intercropping as affected by biological agent application as a technology to increase productivity. This research was arranged in a Factorial Randomized Complete Block Design with an intercropping pattern of hot pepper (two and three rows model). The second factor was the application of biological agents, consisting of Trichoderma asperellum, Bacillus velezensis B-27 and Arbuscular Mycorrhizal Fungi (with and without biological agents). The control was the monoculture of hot pepper without biological agent application. The data observed were analyzed using Analysis of Variance and followed by the Duncan's Multiple Range Test at α= 5 %. The results showed that the relay intercropping of hot pepper produced less numbers of branches and leaves.  It indicated more efficiency in the use of assimilates for the development of generative organs, thereby resulting in the high values fruits weight per plant, which were as high as those in monoculture. The productivity observed in relay intercropping was 12.93 ton.ha-1, which was 15.8 % higher than in monoculture. The application of biological agents significantly increased the stomatal density, the size of stomatal opening, the number of leaves, weight of fruits per plant and productivity of hot pepper. The productivity of plant applied with biological agents was 16.84 ton.ha-1, which was 86.50 % higher than that without biological agents application.